Avaliação do potencial genotóxico e citotóxico associado a queima artesanal da castanha de caju no Município de João Câmara - Galvão, Marcos Felipe de Oliveira (2011)
The Brazil is the third largest producer of cashew nuts in the world. Despite the social and economic importance of the cashew nut, its production is still carried out artisanally. One of the main problems encountered in the cashew production chain are the conditions under which the roasting of the nut occurs to obtain the kernel from the shell. In the present study was conducted a biomonitoring of the genotoxic and cytotoxicity effects associated with the elements from the cashew nut roasting in João Câmara - RN, semi-arid region of Brazil. To assess the genotoxic was used the bioassay of micronucleus (MN) in Tradescantia pallida. In addition, it was performed a comparative between the Tradescantia pallida and KU-20 and other biomarkers of DNA damage, such as the nucleoplasmic bridges (NBP) and nuclear fragments (NF) were quantified. The levels of particulate matter (PM1.0, PM2.5, PM10) and black carbon (BC) were also measured and the inorganic chemical composition of the PM2.5 collected was determined using X-ray fluorescence spectrometry analysis and the assessment of the cytotoxicity by MTT assay and exclusion method by trypan blue. . For this purpose, were chosen: the Amarelão community where the roasting occurs and the Santa Luzia farm an area without influence of this process. The mean value of PM2.5 (Jan 2124.2 μg/m3; May 1022.2 μg/m3; Sep 1291.9 μg/m3) and BC (Jan 363.6 μg/m3; May 70.0 μg/m3; Sep 69.4 μg/m3) as well as the concentration of the elements Al, Si, P, S, Cl, K, Ca, Ti, Cr, Mn, Fe, Ni, Cu, Zn, Se, Br and Pb obtained at Amarelão was significantly higher than at Santa Luzia farm. The genotoxicity tests with T. pallida indicated a significant increase in the number of MN, NBP and NF and it was found a negative correlation between the frequency of these biomarkers and the rainfall. The concentrations of 200 μg/mL and 400 μg/mL of PM2.5 were cytotoxic to MRC-5 cells. All together, the results indicated genotoxicity and citotoxicity for the community of Amarelão, and the high rates of PM2.5 considered a potential contributor to this effect, mainly by the high presence of transition metals, especially Fe, Ni, Cu, Cr and Zn, these elements have the potential to cause DNA damage. Other nuclear alterations, such as the NPBs and NFs may be used as effective biomarkers of DNA damage in tetrads of Tradescantia pallida. The results of this study enabled the identification of a serious occupational problem. Accordingly, preventative measures and better practices should be adopted to improve both the activity and the quality of life of the population. These measures are of fundamental importance for the sustainable development of this activity.